The Implementation of Civic Discourse in Student Group Discussions to Foster Democratic Ethics in the Digital Era - Iqbal, Iqbal; Syafriadi, Syafriadi (TOFEDU: The Future of Education Journal, 2025)
This study aims to examine the implementation of civic discourse in student group discussions as a strategy to develop democratic ethics in the digital era. The digital environment has brought both opportunities and challenges to democratic practices, including the spread of hoaxes, polarization, and hate speech. In this context, it is important for higher education to promote civil dialogue as a part of civic education. The study uses a qualitative case study approach involving students from a civic education program. Data were collected through observation, interviews, and documentation. The findings show that integrating civic discourse in group discussions enhances students’ critical thinking, respectful communication, and digital citizenship. This study concludes that civic discourse is an effective pedagogical tool to cultivate ethical democratic behavior aligned with the demands of the digital age.